The Political Unity of Europe: A Dream or a Reality in the Making? - Patrono, Mario (Victoria University of Wellington Law Review, 2004)
The political unity of Europe is something that most people today see as purely hypothetical, or at the very least, remote: the future appearance on the world stage of a Europe unified politically as well as economically; a Europe that will at last have become a unitary political entity. Many (but not the author) exclude it from the ambit of current political possibility. For some, it is desirable; for others, frightening. This paper considers the "when", and the "if", of European unification – questions to which the eventual coming into force of the Treaty establishing a Constitution for Europe, the text of which was agreed toon 18 June 2004, does not provide an answer.